Skopje - Freeingspace from In-Between the Remembrance and Projectivity - Meri Batakoja (My University, 2018)
The essay is dedicated to four case studies of the city of Skopje, the mega block as context of "NA-MA" department store, the building of central post office, the unfinished cultural center, and the building of the Macedonian government. They are read as a formal underlying logic of the urban fabric developed under different political and economic conditions and at different scales. A range of strategic operations are being discussed as unique efforts to perceive and imagine a city in a particular moment between remembrance and projectivity. The idea for the "freeing space" of these four case studies is behind the projects exhibited at the 16th International Architecture Biennale in Venice 2018.
Keywords: freeingspace, free space, public space, Skopje, International Architecture Biennale, Venice